Chemical Characterization of Carbon Nanoparticles by Titration Method - Ho, Boon Kui (Universiti Malaysia Sarawak (UNIMAS), 2014)
Carbon nanoparticles (CNP) having below 10 nm in size. Firstly, in this study, starch nanoparticles were regenerated from sago starch by adding of starch solution into excess ethanol under controlled condition. After starch nanoparticles were obtained from available native sago starch. Then, it will be converted into carbon nanoparticles through process dehydration with concentrated acid such as sulphuric acid. Finally, carbon nanoparticles can be functionalized by nitric acid oxidation of carbon nanoparticles. The results of fourier transform infrared (FTIR) showed that carbonyl group peaks assigned at 1718 cm-1 and the UV-vis spectrometer showed that the wavelength of carbonyl group at 300 nm. When the concentration of nitric acid and reflux duration increases respectively, the titration method showed that amount of carboxylic groups were also increased. The optimum yield of COOH has been achieved is 1.5 % when carbon nanoparticles refluxed with 2M of nitric acid for 60 minutes.